Faktor Yang Mempengaruhi Pemilihan Moda Transportasi Menuju Sekolah Di Kota Tarakan - Muhammad Kurnia; Iif Ahmad Syarif; Edy Utomo (Borneo Engineering: Jurnal Teknik Sipil, 2025)
Abstract Mode Choice of School Transportation is an important decision influenced by various socio-economic factors and travel characteristics. This study aims to analyze the factors influencing students’ choice of transportation modes to school in Tarakan City, North Kalimantan. Data were collected through a questionnaire survey of 250 student respondents using a purposive sampling method. The findings indicate that motorcycles are the dominant mode of transportation (89.3%) chosen by students. The most influential factors in mode choice are speed (67.9%), comfort (60.7%), and low cost (39.3%). The analysis also reveals that the majority of students (82.1%) do not possess a driver’s license, yet they still use motorcycles due to accessibility and flexibility. Willingness to switch to public transportation is low because of the limited availability and poor service quality of public transport in Tarakan City. This study recommends the development of a public transportation system that is comfortable, well-scheduled, and affordable to encourage behavioral change among students in their transportation choices. Keywords: transportation mode, students, mode choice, Tarakan City, motorcycle   Abstrak   Pemilihan moda transportasi menuju sekolah merupakan keputusan penting yang dipengaruhi oleh berbagai faktor sosial-ekonomi dan karakteristik perjalanan. Penelitian ini bertujuan untuk menganalisis faktor-faktor yang mempengaruhi pemilihan moda transportasi oleh pelajar menuju sekolah di Kota Tarakan, Kalimantan Utara. Data dikumpulkan melalui survei kuesioner kepada 250 responden pelajar dengan menggunakan metode purposive sampling. Hasil penelitian menunjukkan bahwa sepeda motor merupakan moda transportasi dominan (89,3%) yang dipilih oleh pelajar. Faktor-faktor yang paling berpengaruh dalam pemilihan moda adalah kecepatan (67,9%), kenyamanan (60,7%), dan biaya yang murah (39,3%). Analisis menunjukkan bahwa mayoritas pelajar (82,1%) tidak memiliki Surat Izin Mengemudi (SIM), namun tetap menggunakan sepeda motor karena kemudahan akses dan fleksibilitas. Kesediaan beralih ke transportasi umum rendah karena keterbatasan ketersediaan dan kualitas layanan angkutan umum di Kota Tarakan. Penelitian ini merekomendasikan perlunya pengembangan sistem transportasi umum yang nyaman, terjadwal, dan terjangkau untuk mendorong perubahan perilaku transportasi pelajar. Kata kunci: moda transportasi, pelajar, pemilihan moda, kota tarakan, sepeda motor